The Authority Of Public Notary In The Making Of Deregistration Agreement Of Mortgage Right - Gholib Ivan Ali; Riskha Amaliya Lubis; Anis Mashdurohatun (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
Deregistration in the legal dictionary means deletion. The deletion in question is the abolishment of the mortgage right on the land title book and the certificate. If the mortgage right is removed, the Land Office shall make deregistration (Deletion/Roya) to the record of mortgage rights on the land title book and its certificates. The method used by the writer in this research was sociological juridical research, with descriptive analytical research specification, while the data analysis method used was qualitative analysis. Based on the results of the study and discussion, it can be concluded that the Deregistration Consent Agreement is as a statement from the debtor in notarial, the content is about the debtor has paid off the debt and the creditor agreed to remove the certificate of land rights burdened by the Guaranteed Right to be a clean certificate of any engagement. The Deregistration Consent Agreement does not have the executorial power as the Mortgage Right Certificate. The authority of a Notary in making the Deregistration Consent Agreement shall be based on the statement of the debtor before the Notary, so that the statement or agreement is conveyed by the Notary in an authentic agreement. This is in accordance with the provisions of Article 15 paragraph (1) of Act No.2 Of 2014 on Amendment to Act No.30 Of 2004 regarding Notary Position.Keywords: Public Notary; Agreement; Mortgage Rights.